Effects of microclimatic factors on stomatal conductance of plants in vertical greenery systems in humid subtropical areas. (October 2022) - Yan, Junru; Zhao, Lihua; Zhang, Yu; Liu, Mingxin; Yang, Yuanqin; Liu, Zhixin; Zhang, Lei
Highlights: Reduced irrigation in winter does not significantly affect VGS. The transpiration in winter is about 1/3 of that in other seasons. The E of southwest-oriented VGS is 41% higher in the afternoon than morning. A stomatal model in VGS in humid subtropical areas is proposed. Abstract: Plant transpiration through stomata is crucial in land surface physical processes and the hydrosphere-atmosphere-biosphere water vapor cycle. Applying stomatal models to vertical greenery systems (VGSs) is challenging because of the unique plant habitat. However, VGSs are widely used in subtropical areas; thus, plant transpiration in these systems should be investigated. Field measurements are used to determine the relationship between stomatal conductance ( g s ) and different microclimatic factors: solar radiation ( I ), air temperature ( T a ), relative humidity (RH), and soil volumetric water content ( θ ). A stomatal model based on multiple nonlinear regression is proposed, and its accuracy for different VGS plant species is verified with field measurements. The model's root mean square error (RMSE) is 57% lower than that of existing models. The latent heat flux from transpiration ( E ) of VGS in different seasons and orientations are calculated, and design strategies are proposed to utilize the cooling potential of VGS better. The prediction accuracy of the water vapor transfer, thermal comfort, and building energy consumption can be improved by incorporating the proposed model into an urban canopy model (UCM) and building energy model (BEM). It will provide guidelines for sustainable urban planning and VGS design regarding heat island mitigation and building energy savings.